1995
DOI: 10.1099/00207713-45-2-351
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Analysis of the Genus Saccharomonospora Conducted with 16S rRNA Gene Sequences

Abstract: Nearly complete sequences of 16s rRNA genes of representative strains of the genus Saccharomonospora were determined following the isolation and cloning of the amplified genes. The sequences were aligned with those of representatives of the family Pseudonocardiaceae, and a phylogenetic tree was inferred by the neighborjoining method. The genus Saccharomonospora formed a distinct clade within the evolutionary radiation encompassed by the family Pseudonocardiaceae. The average nucleotide similarity value found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 26 publications
2
39
1
1
Order By: Relevance
“…Table 1 shows the strain designations and the GenBank accession numbers for the 16S-23s and 23S-5s ITS sequences. The sources of strains have been described previously (12,39).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows the strain designations and the GenBank accession numbers for the 16S-23s and 23S-5s ITS sequences. The sources of strains have been described previously (12,39).…”
Section: Methodsmentioning
confidence: 99%
“…(14). Recently, a 16s ribosomal DNA (rDNA) sequence analysis showed that the genus Saccharomonospora is a distinct phyletic group within the evolutionary radiation of the family Pseudonocardiaceae (12). However, the 16s rDNA sequences of the four validly described Saccharomonospora species exhibited relatively high levels of nucleotide similarity (97.5% * 1.0%), and the levels of homology between strains of the same species were high.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The ssDNA templates produced were directly used for the sequencing reaction. The sequencing was performed as described previously (Kim et al, 1995) using a-35S-labelled dATP and a DNA sequencing kit (US Biochemical). The sequencing primers were derived from conserved regions of previously described 16s rRNA gene sequences of eubacteria.…”
Section: Methodsmentioning
confidence: 99%